A dimensão formadora das práticas de escrita de professores - Côco, Valdete (2006)
This study is focused on the teacher s writing investigating the way it shows up on written registers of the teachers work and which are the references through this systematization. We inquire in brief: How do teachers use the writing within their professional context? This issue is investigated observing the senses established through the written practices as ways of its materiality, the conditions on which the written acts are effectivated by teachers. The work in the school and the participation in processes of continued learning are integrated to the dynamics of the teacher s life, observing the confront to the demands of the writing and the responsive processes. Anchored on the theoric methodological of Bakhtin and Certeau, the study has as antecedents the language in its social dimension, the relations among writing, values and the social pleadings and the learning as a continuing process among others. The qualitative research having an ethnographic characters involving working teachers from 5th to 8th grade Fundamental teaching linked to the Public School Teaching of Vitória Espírito Santo. Data were collected through observation, at meetings of continued learning, inquiries, interviews and consulted materials. The research points out to teachers are facing new challenges according to written practices. At work, the senses to written practices constitute a complexity which involve the confronting among effective of the work with its own repertoire (planning, evaluations, formularies, report, projects, etc) and the expectations of integration within levels that, in a general way present the academics and scientific text as a reference for the continuity of the studies, for the participation in congresses and seminaries and for the visibility and the recognition of the teacher work. The private practices of writing they return to practices of life administration (messages, lists, notes, etc) and, on critical moments, as process of elaboration of conflicts, through letters, poetries mainly. Because of the demands lived by teachers, the space of continued learning presents itself as a space in which the teachers experience some activities of writing and they ve got the dimensions of their work linked with a social dynamic of development turistically written, as practices linked to the material conditions of the teaching process, the written practices relate themselves with limited time conditions in the set of pleadings which the teachers are called to answer the daily professional life. The research reveals the dynamic of teacher s work with the desire to participate into the privileged spaces of conversations under the written form and with different processes of appropriation of written practices which integrate the tense game of fighting for the produced assets by humanity.